Microbial Communities of Hydrothermal Guaymas Basin Surficial Sediment Profiled at 2 Millimeter-Scale Resolution - Engelen, Bert; Nguyen, Tien; Heyerhoff, Benedikt; Kalenborn, Saskia; Sydow, Katharina; Tabai, Houssem; Peterson, Richard N.; Wegener, Gunter; Teske, Andreas (Frontiers in Microbiology, 2021)
The surficial hydrothermal sediments of Guaymas Basin harbor complex microbial communities where oxidative and reductive nitrogen, sulfur, and carbon-cycling populations and processes overlap and coexist. Here we resolve microbial community profiles in hydrothermal sediment cores of Guaymas Basin on a scale of 2 millimeters, using Denaturing Gradient Gel Electrophoresis (DGGE) to visualize the rapid downcore changes among dominant bacteria and archaea. DGGE analysis of bacterial 16S rRNA gene amplicons identified free-living and syntrophic deltaproteobacterial sulfate-reducing bacteria, fermentative Cytophagales, members of the Chloroflexi (Thermoflexia), Aminicenantes, and uncultured sediment clades. The DGGE pattern indicates a gradually changing downcore community structure where small changes on a 2-millimeter scale accumulate to significantly changing populations within the top 4 cm sediment layer. Functional gene DGGE analyses identified anaerobic methane-oxidizing archaea (ANME) based on methyl-coenzyme M reductase genes, and members of the Betaproteobacteria and Thaumarchaeota based on bacterial and archaeal ammonia monooxygenase genes, respectively. The co-existence and overlapping habitat range of aerobic, nitrifying, sulfate-reducing and fermentative bacteria and archaea, including thermophiles, in the surficial sediments is consistent with dynamic redox and thermal gradients that sustain highly complex microbial communities in the hydrothermal sediments of Guaymas Basin.